The Potential Role of Combination Pharmacotherapy to Improve Outcomes of Pediatric Obesity: A Case Report and Discussion - Fox, Claudia K.; Kelly, Aaron S. (Frontiers in Pediatrics, 2018)
There is a gap in treatment modalities for pediatric patients with obesity for whom lifestyle modification therapy, on the one hand, may be insufficient to meaningfully reduce BMI, and bariatric surgery, which on the other hand, may not be indicated, available or desired. Although pharmacotherapy may help fill this treatment void, there is a paucity of FDA-approved medications indicated for pediatric obesity and further, most are single agents with only modest mean treatment effects. In contrast, combination pharmacotherapy, such as phentermine/topiramate, appears to offer greater weight loss efficacy in adults and may prove to be superior to monotherapy for pediatric patients as well. This case report describes the clinical management of severe obesity in a 10 year old girl with lifestyle modification therapy and subsequent addition of first topiramate and later phentermine. Using the case as a platform, the current state of pharmacotherapy for pediatric obesity will be described thereby highlighting the limited efficacy of single agents. Additionally, the biological rationale for combination pharmacotherapy, including potential mechanisms which may account for the poor response to single agents, will be discussed.